1999
DOI: 10.1103/physrevb.59.11183
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Raman scattering in disorderedBi2Sr2Ca(

Abstract: Electronic Raman scattering has been studied in single-crystal Bi 2 Sr 2 Ca(Cu 1Ϫx Fe y ) 2 O ␦ for different Fe concentrations. The 2⌬ peak positions of the B 1g and A 1g channels in the superconducting state are only slightly affected by impurity scattering with the ratio B1g / A1g unchanged. There is also no low-frequency threshold at any impurity concentration. These two features are consistent with unconventional pairing. However, the crossover scale to a cubic dependence in the B 1g channel, contrary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 16 publications
1
17
1
Order By: Relevance
“…: this is in clear contradiction to all the experiments, most studies showing the magnitude of the A 1g peak being even larger than the B 1g one[1,2,[16][17][18][19].…”
contrasting
confidence: 62%
“…: this is in clear contradiction to all the experiments, most studies showing the magnitude of the A 1g peak being even larger than the B 1g one[1,2,[16][17][18][19].…”
contrasting
confidence: 62%
“…6(b), we plot T c versus the energy of this mode ω res , determined by neutron scattering for various cuprate systems [15][16][17][18]. We also include the peak energy ω A1g of the A1 g mode observed in Raman scattering [19][20][21][22], which closely follows the resonance mode energy. We see an impressive linear dependence of T c on ω res and ω A1g for wide variety of cuprates.…”
Section: Excitation: Magnetic Resonance Mode As a Roton Analoguementioning
confidence: 99%
“…4 He observed by neutron scattering [60]. (b) The plot of Tc versus energy of the roton minimum of bulk superfluid 4 He (values for both axes multiplied by a factor 60) measured under applied pressures [61], compared with the relationship seen in HTSC systems for the energies of the neutron resonance mode at (π, π) [15][16][17][18] and the Raman A1g mode [19][20][21][22]. Also included are the neutron energy transfers at the (π ± δ, π) point in YBCO [17] and LSCO [62].…”
Section: Acknowledgmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The independence of disorder for the polarization dependence has been reported for Fe-doped Bi2212. 16 However, apart from unchanged ratio of the peak frequencies in different symmetry channels, the experimental check of Devereaux's theory showed that a low-frequency portion of the spectrum, as a function of disorder, follows the behavior expected for an s wave. Namely, the spectral weight of the low-frequency portion of the spectra appeared to shift to lower rather than to higher frequencies.…”
mentioning
confidence: 95%